2022
DOI: 10.33448/rsd-v11i9.31370
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficiência da laparotomia pelo flanco para obtenção de biópsias intestinais em equinos

Abstract: Este estudo teve por objetivo avaliar a eficiência da laparotomia pelo flanco para obtenção de biópsias intestinais em equinos, bem como a ocorrência de complicações associadas ao procedimento. Foram utilizados 16 equinos adultos hígidos, sem raça definida, quatro machos e 12 fêmeas, com idade variando entre quatro e 14 anos e peso corporal médio de 248,40 + 2,28 kg. Todos os animais foram submetidos a duas laparotomias pelo flanco para coleta de biopsias intestinais, jejuno e cólon maior, com intervalo de 144… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Regarding the surgical procedure, no complications were observed in phase 1 of the experiment, except for the development of edema or seroma/infection in the incisional line, regardless of the group, as described by Melo et al (2022a). Protopapas (2000 observed that complications affecting the incision in horses treated surgically for the treatment of gastrointestinal disorders were closely associated with negative energy balance in the horse (Naylor et al, 1980), metabolic alteration invariably associated with absence or low food intake.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Regarding the surgical procedure, no complications were observed in phase 1 of the experiment, except for the development of edema or seroma/infection in the incisional line, regardless of the group, as described by Melo et al (2022a). Protopapas (2000 observed that complications affecting the incision in horses treated surgically for the treatment of gastrointestinal disorders were closely associated with negative energy balance in the horse (Naylor et al, 1980), metabolic alteration invariably associated with absence or low food intake.…”
Section: Resultsmentioning
confidence: 84%
“…This study was part of a larger experiment developed with the purpose of evaluating the metabolic and gastrointestinal mucosal response of horses subjected to starvation after exploratory laparotomy, and some results were previously published (Melo et al, 2021;2022a, 2022bFerreira et al, 2022;Melo et al, 2022ab). Kidney and liver function parameters remained constant throughout the experimental period, with only fasting hyperbilirubinemia being observed in animals from the ENTFL, ENTGL and PARFL groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation